In vitro Antioxidant and Radical Scavenging Capacities of Extracts from Tinospora cordifolia - Athar Abbasi, Muhammad; Nadeem Asghar, Muhammad; Irshad, Misbah; Najaf, Sadia; Ullah Khan, Islam; Zia, Iram (Asian Journal of Chemistry, 2010)
The aim of this investigation is to study the in vitro antioxidant and radical scavenging activity of Tinospora cordifolia (Willd.) extracts. The antioxidant components were initially extracted in methanol and subjected to fractionation in solvents of different polarity. The chloroform soluble fraction was then subjected to column chromatography using n-hexane with a gradient of chloroform upto 100 %, followed by methanol. Antioxidant potential and radical scavenging activity of the 12 fractions obtained from the column were investigated employing different antioxidant assays such as 2,2'-azinobis(3-ethylbenzo-thiazoline-6-sulphonic acid) (ABTS) radical cation scavenging, ferric reducing antioxidant power (FRAP), 2,2-diphenyl-1-picrylhydrazil (DPPH) scavenging, total phenolic content (TPC) and total antioxidant activity determination using ferric thiocyanate method. Using ABTS•+ decolourization assay and FRAP assay, T. cordifolia extracts showed a wide range of antioxidant activity. Trolox equivalent antioxidant capacity (TEAC) and FRAP values for various fractions ranged from 0.003-7.654 mM of trolox equivalents and 126.88-1516.80 mg/L of FeSO4 equivalents, respectively. Using total phenolic content assay the amount of total phenolics for different fractions of T. cordifolia ranged from 4.84 ± 0.21-107.27 ± 1.37 mg/L. No significant co-relation was found between TPCs and TEAC (r2 = 0.652) and FRAP assay (r2 = 0.686). The EC50 values determined by using DPPH radical scavenging assay ranged from 83.26-588.31 μg of dried weight (DW)/mL of DPPH solution. Employing inhibition of lipid peroxidation assay by ferric thiocyanate method, the extracts showed inhibition of lipid peroxidation comparable to trolox. On the basis of the results obtained here, T. cordifolia may be considered as a rich source of antioxidants.